Effect of Osteoking on the osteogenic and adipogenic differentiation potential of rat bone marrow mesenchymal stem cells in vitro - Congtao Yu; Lifen Dai; Zhaoxia Ma; Hongbin Zhao; Yong Yuan; Yunfeng Zhang; Pengfei Bao; Yanfang Su; Daiping Ma; Change Liu; Xingfei Wu; Jinxue Liu; et al. (BMC, 2019)
Abstract Background Bone damage is a condition that affects the quality of life of patients. Mesenchymal stem cells (MSCs) are important for bone repair. Osteoking is a natural compound in traditional Chinese Medicine used to treat bone diseases; however, the effect of Osteoking on the differentiation of MSCs has not been reported. In this study, we aimed to investigate the effect of Osteoking on the osteogenic and adipogenic differentiation potential of rat bone marrow mesenchymal stem cells (rbMSCs). Methods The effects of Osteoking on the proliferation and differentiation of rbMSCs were investigated. Different concentrations of Osteoking were prepared, and its cytotoxicity was evaluated by CCK-8 assay. The expression of osteogenic and adipogenic genes were determined, and several staining methods were used to reveal the osteogenic and adipogenic differentiation potential of rbMSCs. Results Our results show that appropriate concentrations of Osteoking can enhance osteogenic differentiation of rbMSCs and reduce adipogenic differentiation without any effect on proliferation. This may be related to the changes in related gene expression. Conclusion Osteoking enhances osteogenic differentiation and inhibits adipogenic differentiation of rbMSCs. Therefore, Osteoking may have a therapeutic potential for treating bone disease caused by changes in differentiation function of MSCs.